Religious Moderation Literacy: A Study of Christian Religious Education at YPPGI Sentani Junior High School - Balyo, Assor; Malatuny, Yakob Godlif; Bu’tu, Dorce; Kabanga, Lewi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study analyzes religious moderation literacy in Christian Religious Education at YPPGI Sentani Junior High School. Focusing on the context of diversity in Indonesia, this study aims to evaluate students' understanding and the effectiveness of teaching methods that promote the values of tolerance, inclusivity, and moderation. With a qualitative descriptive approach, data were collected through in-depth interviews, participatory observations, and analysis of curriculum documents. The results of the study show that religious moderation literacy has been applied through the teaching of peaceful values and respect for differences. However, there are challenges, including limited resources and a lack of a deep understanding of religious moderation. These findings confirm the importance of effective teaching strategies to improve students' moderate attitudes in daily life. This study makes a significant contribution to building a tolerant and harmonious generation, especially in a multicultural environment such as Papua, through strengthening the role of Christian religious education as a means of religious moderation literacy